Total saliva pH in patients with periodontal disease of UNMSM Dental Faculty Periodontal Service. - García Linares, Sixto (2008)
The present study evaluates the relationship between salivary pH and periodontal disease. Sixty patients (30 gingivitis patients and 30 periodontitis patients) who went to UNMSM Dental School were evaluated. Also, we took a control group that included 20 dental students with healthy periodontum. We evaluated periodontal status and salivary samples were taken before and after phase I treatment. It was found a difference between control group that presented an average pH of 6.9 and gingivitis and periodontitis groups that showed values of 7.3 and 7.9 respectively. After treatment, patients who had a positive evolution presented a decrease in their salivary pH levels in comparison with control group that maintained its initial value. Gingivitis patients presented an average decrease of 0.3 (7.3 to 7.0). In periodontitis group patients, pH decreased from 7.9 to 7.3. This study concludes that salivary pH shows higher values in patients with periodontal disease and it decreases after the realization of an appropriate periodontal treatment.